Persepsi Tamu Terhadap Penggunaan Teknologi di Hotel-Hotel Yogyakarta Menuju Pariwisata Cerdas - Hananto, Kombang (Jayapangus Press, 2023)
The aim of this research is to determine the extent to which hotels in Yogyakarta use modern technological devices for more profitable, effective and efficient hotel operations, and at the same time leading to smart tourism. The research was conducted between 2022. In this research, only 4 star hotels and 5 star hotels were selected in the Special Region of Yogyakarta. The population of 4 star and 5 star hotels is 46 hotels. Using the standard method for determining the number of samples, the number of samples for this research has been calculated as 14 hotels consisting of 7 5 star hotels and 7 4 star hotels. Sampling for questionnaire data was carried out on guests staying at these 14 hotels. Using the Raosoft method, the sample size for this research was 214 respondents. It is assumed, that the use of technology has a positive influence on hotel services, but only as a way to make better services provided by employees (assuming that they are trained and motivated to use it) and that technology cannot and should not replace the human factor. From the results obtained, almost all hotels studied all use the latest technological devices and there is a strong correlation between convenience and usefulness and satisfaction in using technological devices in hotels. The results of the smartPLS bootstrapping analysis state that the alternative hypothesis is accepted or rejects the null hypothesis, in other words it can be stated that there is a significant relationship both individually and jointly between the ease and usefulness of using modern technology in hotels and guest satisfaction in using modern technology in hotels.